Identity Crisis as the Main Motive of Contemporary Native American Literature - Sergii Rudenko; Yaroslav Sobolievskyi (International Society of Philosophy and Cosmology, 2021)
This research offers a linguacultural analysis of the main ideas and goals of institutions for the preservation of the culture and language of the Indigenous peoples of America, through the publication of relevant research in thematic journals and popular books, to determine the relevance of the problem of the identity crisis in the worldview and literature of Native Americans. The authors used the thick description method to analyse the main goals of twenty-five Native American organisations, basing their research on articles published in the past few years in nine scientific journals on various topics (from culture to business) and books written by Indigenous authors. The authors reached their conclusions based on this research material. The results of the study, which focused on institutions that preserve the culture and heritage of the Indigenous peoples of America and their activities, found that one of the main challenges is the preservation of identity. Analysis of the articles of leading journals on literature, culture, politics, business, philosophy, as well as analysis of the content of the books written by Indigenous people, revealed that identity crisis is an urgent problem. Despite the prevailing opinion in American society, it is obvious that a crisis is inevitable. All 25 of the organisations, whose goals were studied in this article, support, preserve, broadcast, and transmit values, heritage, and spiritual culture, and, in one way or another, confront the identity crisis. After analysing more than 550 articles in nine scientific journals devoted to the culture of American Indians, it was found that the vast majority of materials directly or indirectly relate to the problem of the crisis. To count the exact number of articles in which this problem is raised, in our opinion, is impossible due to subjective views, but we argue that this percentage is very significant. Almost all materials in one way or another relate to the problem of an identity crisis.